Scope of medical rigid thoracoscopy in patients with pleural effusion of unknown etiology: A prospective single center study - Namrata; Amarendra Kumar Shukla; Tiwari, Pawan; Veerendra Arya; Prahlad Prabhudesai (Asian Journal of Medical Sciences, 2023)
Background: Pleural diseases commonly encountered are pleural effusion, pneumothorax, pleural wall thickening, and pleural mass. Medical thoracoscopy is a minimally invasive procedure that allows diagnostic and therapeutic intervention. The medical diagnostic thoracoscopy in local anesthesia is a simple, low-cost investigation with relatively high diagnostic accuracy, no mortality, and low morbidity. A diagnosis of pleural tuberculosis (TB) could be achieved in 99% of patients as against 51% using closed pleural biopsy. Aims and Objectives: Assessment of the role of medical rigid thoracoscopy in patients with pleural effusion of unknown etiology in a tertiary health care setup. The primary objectives of the study were to evaluate the diagnostic yield of medical thoracoscopy in pleural effusion of unknown etiology. Materials and Methods: The study duration/time frame to address the study: November 2017–February 2019 sample size with Justification Sample size: Minimum 31 patients. It was a prospective observational study. All patients admitted in hospital/daycare at LHRC presenting with pleural effusion with unknown etiology. All patients had a medical thoracoscopy, and samples were sent for microbiological and histological analysis. Clinical, thoracoscopic results and histopathological data of the patients were collected prospectively and analyzed. Results: In this study, 28 patients out of 31 patients were diagnosed. The diagnostic yield of thoracoscopic pleural biopsy was 90.3% Out of 31 patients, the most common complication found was chest pain 48.4% (15/31), followed by 09.7% (03/31) of the cases had complications such as surgical emphysema, postoperative fever, and bleeding. There were no complications in 32.2% (10/31) patients. Conclusion: Medical thoracoscopy is a noble procedure that helps the pulmonologist/surgeon to inspect the pleural cavity. It is a safe and effective diagnostic as well as a therapeutic tool with a high diagnostic yield. The most common differentials of undiagnosed pleural effusion cases are TB and malignancy.